Pengaruh Kompetensi, Komitmen dan Etika Auditor Terhadap Kinerja Auditor Internal pada Kantor Inspektorat Aceh - Sarboini; Rahmah Yulianti; Rahma Try Fajri (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2022)
This study aims to determine the effect of auditor competence, commitment and ethics on the performance of internal auditors at the Aceh Inspectorate Office, either simultaneously or partially. The population in this study are auditors who work at the Aceh Inspectorate Office. Total population of 47 people. The sampling method used is the Census because it involves the entire population as research respondents. The samples taken in this study were 47 people. The data used in this study is multiple linear regression. The results of the study show that auditor competence, commitment and ethics simultaneously influence the performance of internal auditors at the Aceh Inspectorate Office. The correlation coefficient (R) = 0.779 which indicates that the degree of relationship (correlation) between the independent variables and the dependent variable is 77.9%. This means that the performance of internal auditors at the Aceh Inspectorate Office is very closely related to the factors of education, training, years of service and the R2 coefficient value is obtained by a value of 0.580 which means it influences the auditor's performance at the Aceh Inspectorate Office. While the partial results of the study also reveal that auditor competence, commitment and ethics affect the performance of internal auditors at the Aceh Inspectorate Office, this proves that auditor competence, commitment and ethics have an influence on auditor performance at the Aceh Inspectorate Office.